Crystallization and preliminary X‐ray diffraction analysis of an active‐site mutant of `loopless' family GH19 chitinase from Bryum coronatum in a complex with chitotetraose. Issue 12 (1st December 2013) - Ohnuma, Takayuki; Umemoto, Naoyuki; Taira, Toki; Fukamizo, Tamo; Numata, Tomoyuki
<x xml:space="preserve">Abstract</x> The catalytic mechanism of family GH19 chitinases is not well understood owing to insufficient information regarding the three‐dimensional structures of enzyme–substrate complexes. Here, the crystallization and preliminary X‐ray diffraction analysis of a selenomethionine‐labelled active‐site mutant of `loopless' family GH19 chitinase from the moss Bryum coronatum in complex with chitotetraose, (GlcNAc)4, are reported. The crystals were grown using the vapour‐diffusion method. They diffracted to 1.58 Å resolution using synchrotron radiation at the Photon Factory. The crystals belonged to the monoclinic space group C2, with unit‐cell parameters a = 74.5, b = 58.4, c = 48.1 Å, β = 115.6°. The asymmetric unit of the crystals is expected to contain one protein molecule, with a Matthews coefficient of 2.08 Å3 Da−1 and a solvent content of 41%.